DIFFERENCES OF EFFECTIVENESS OF COOPERATIVE LEARNING LEARNING MODEL TYPE TEAMS GAMES TOURNAMENT (TGT) AND GROUP WORKING ON LEARNING RESULT AT ELEMNTARY SCHOOL - Heru Mudiyanto (IKIP Siliwangi, 2017)
This research is based on the general problem, that is how the effectiveness of the implementation of cooperative learning model type TGT and group learning method to improve learning outcomes in social studies subjects in grade VI of elementary school in the aspect of knowledge, understanding and application, and to see if there are differences Significance between cooperative learning method of TGT type with ordinary group learning method. The research method used is quasi experiment with sample of student of class VI of SD Negeri Selaawi I and II. Research instrument in the form of learning result test. The hypothesis was tested using Mann-Whitney U test with a significance level of 0.05. The result of this research is TGT model can improve learning outcomes and more effective than the usual group work model. Keywords: learning model, cooperative learning type TGT, group work.